DEVELOPMENT OF PRODUCT PACKAGING DESIGN IN INCOME INCREASING BUSINESS GROUP OF PROSPER FAMILY (UPPKS) FRIENDS KITCHEN IN BATAM CITY: Pengembangan Desain Kemasan Produk Pada Kelompok Usaha Peningkatan Pendapatan Keluarga Sejahtera (UPPKS) Sahabat Kitchen Di Kota Batam - Dian Lestari Siregar; Mohamad Gita Indrawan; Anggia Dasa Putri; Evan Rosiska; Raymond Raymond (ASOSIASI IDEBAHASA KEPRI, 2023)
This training aims to develop product packaging designs. This community service activity is carried out in the Sahabat Kitchen business group to increase the income of prosperous families (UPPKS) with the aim of: 1) Expanding the market share for its products, 2) Increasing expertise and understanding in the field of product and packaging design 3) Increasing productivity. This activity is applied to community education with training techniques. The training includes mentoring, discussion. The result of these activities is that participants have an understanding of Product Packaging Design Development.